Dual-Band Metasurface-Based Decoupling Method for Two Closely Packed Dual-Band Antennas - Liu, Feng; Guo, Jiayin; Zhao, Luyu; Huang, Guan-Long; Li, Yingsong; Yin, Yingzeng (IEEE transactions on antennas and propagation, 2020)
In this communication, a metasurface-based decoupling method (MDM) is proposed to reduce the mutual couplings at two independent bands of two coupled multiple-input-multiple-output (MIMO) antennas. The metasurface superstrate is composed of pairs of non-uniform cut wires with two different lengths. It is compact in size and effective in decoupling two nearby dual-band patch antennas that are strongly coupled in the H-plane with the edge-to-edge spacing of only 0.008 wavelength at low-frequency band (LB). The antenna is fabricated and measured and the results show that the isolation between two dual-band antennas can be improved to more than 25 dB at both 2.5-2.7 GHz and 3.4-3.6 GHz bands, while their reflection coefficients remain to be below -10 dB after the metasurface superstrate is introduced. Moreover, the total efficiency is improved by about 15% in the low band and the envelope correlation coefficient (ECC) between the two antennas is reduced from 0.46 to 0.08 at 2.6 GHz and 0.08 to 0.01 at 3.5 GHz. The proposed method can find plenty of applications in dual-band MIMO and 5G communication systems.